Fenomena Pengaruh Dukungan Keluarga Terhadap Kepuasan Kerja Perempuan Sebagai Upaya Kesetaraan Gender Pada PT Citilink Indonesia - Endri Haryati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
There is much debate about the existence of job satisfaction caused by gender differences. It is argued that women feel higher job satisfaction than men even in jobs that are objectively bad. This difference in job satisfaction between women and men is very relevant, this is because women feel more satisfied because they are more focused on their role as housewives than their role as workers. One factor that affects women's dual role conflict is family support. The higher the family support, the dual role conflict will decrease and vice versa if the family support is low, the dual role conflict will be high. When there is a change in perspective on the roles of women and men, there is likely to be a shift in job satisfaction in women and men.